Local Election of Solo 2024: Looking at the Role of Political Parties and Coalitions Behind the Scenes - Athaya Syifa Nadira Kusuma; Putri Rohmaning (Journal of Religion, Local Politics, and Law, 2025)
The 2024 Solo City Regional Head Election (Pilkada) is an interesting political event to study, especially regarding the role of political parties (parpol) and coalitions in determining the dynamics of contestation. This research aims to analyze the strategies, alliances, and political interactions built by political parties and coalitions behind the scenes of the 2024 Solo Regional Head Election. Using a qualitative approach and case study method, this research will explore the factors that influence coalition formation, inter-political negotiations, and their impact on the local democratic process. Data collection was conducted through in-depth interviews with various sources, participatory observation, and analysis of official documents related to Pilkada. The results of the study are expected to reveal the complexity of the role of political parties and coalitions in the 2024 Solo Election and contribute to the understanding of local political dynamics and the strengthening of the democratic system in Indonesia